2008
DOI: 10.1055/s-2008-1034278
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activities of Flavonoid Glycoside Acetates from Consolida oliveriana

Abstract: The flavonoids kaempferol, quercetin, trifolin, hyperoside 2''- and 6''- acetates, 7-glucotrifolin, biorobin and robinin were isolated from the aerial parts of Consolida oliveriana. Their derivatives kaempferol tetraacetate, quercetin pentaacetate, trifolin heptaacetate and hyperoside octaacetate exhibited significant cytotoxicity IN VITRO against three human cell lines HL-60, U937 and SK-MEL-1 while hyperoside 2''-acetate, hyperoside-6''-acetate, glucotrifolin decaacetate and heptamethyltrifolin were inactive. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Natural compounds from fruits, vegetables, and grains, possess anti-cancer properties and represent a promising therapeutic approach for the prevention and treatment of many cancers [Kawasaki et al, 2008]. The anti-tumor activities of the natural compounds have recently attracted much attention [Diaz et al, 2008;Khan et al, 2008;Kim et al, 2010]. In the present study, we found that polydatin, a natural small compound, exhibited significant cytotoxicity in various human tumor cell lines.…”
mentioning
confidence: 52%
“…Natural compounds from fruits, vegetables, and grains, possess anti-cancer properties and represent a promising therapeutic approach for the prevention and treatment of many cancers [Kawasaki et al, 2008]. The anti-tumor activities of the natural compounds have recently attracted much attention [Diaz et al, 2008;Khan et al, 2008;Kim et al, 2010]. In the present study, we found that polydatin, a natural small compound, exhibited significant cytotoxicity in various human tumor cell lines.…”
mentioning
confidence: 52%
“…and UV/Visible spectroscopy and mass spectrometry). The details of the isolation have been published recently [13]. Stock solutions of 10 mM TA were made in dimethyl sulfoxide (DMSO) and aliquots were frozen at -20°C.…”
Section: Reagentsmentioning
confidence: 99%
“…1a), a flavonoid derivative which was obtained by acetylation of the natural product trifolin [13]. Antiproliferative studies on TA indicate that this compound displays similar cytotoxic properties in all cell lines assayed (IC 50 * 10 lM at 72 h).…”
Section: Ta Induces Apoptosis On Human Myeloid Leukaemia Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids have recently gained attention due to their antitumor activity (9)(10)(11). Icaritin is a prenylflavonoid and is a hydrolytic product of icaritin, derived from Herba Epimedii.…”
Section: Introductionmentioning
confidence: 99%